Hak Azazi Manusia di Era Demokrasi dalam Perspektif Hukum Islam - Multazim A.A (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
Human rights in Islam contains the basic principles of parity, freedom and respect for fellow human beings. The equation, meaning that Islam looks at all the human equivalent, the difference is achievement ketakwaanya. Thus it can be understood that human rights in Islam is defined as basic human rights – rights that are conferred by God Almighty. So human rights in Islam have a characteristic: 1) sourced from revelation, 2) not absolute because it is limited by respect for the freedom of other people's interests/3) right not to be separated from obligations.